NiMoO4 / Ni3S2 electro-catalytic material loaded on foamed nickel as well as preparation method and application of NiMoO4 / Ni3S2 electro-catalytic material
The NiMoO4/Ni3S2 electrocatalytic material on nickel foam, prepared via a two-step hydrothermal process, addresses the inefficiencies of urea oxidation by achieving low voltage operation, enhancing the urea oxidation reaction's efficiency and reducing energy consumption.
Patent Information
- Application Number
- CN202411252229.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The high initial oxidation potential and slow kinetics of the urea oxidation reaction (UOR) limit its efficiency and increase energy consumption, necessitating the development of non-precious metal catalysts with low initial potential and high catalytic efficiency for urea oxidation.
A method for preparing a NiMoO4/Ni3S2 electrocatalytic material loaded on nickel foam through a two-step hydrothermal process using inexpensive and readily available raw materials, involving treatments with nitric acid, ethanol, and deionized water, followed by hydrothermal reactions with Na2S2O3 and Ni(NO3)2·6H2O and Na2MoO4·2H2O.
The prepared NiMoO4/Ni3S2 electrocatalytic material achieves a low operating voltage of 1.338V (vs. RHE) for 10 mA cm-2 current density and 1.357V for 100 mA cm-2 in a urea oxidation reaction, reducing energy consumption.
Smart Images

Figure CN119121272A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic materials, and in particular relates to a NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam, a preparation method and an application thereof. Background Art
[0002] With the current energy crisis and the demand for environmental protection, it is urgent to find clean renewable energy. Hydrogen, as an ideal clean energy, has attracted much attention, but how to reduce its preparation cost is the primary issue. Urea oxidation reaction (UOR) can replace OER in water electrolysis to couple with cathode hydrogen evolution reaction (HER) because its thermodynamic potential is lower than that of traditional oxygen evolution reaction (OER), thus reducing the energy consumption of hydrogen production and contributing to the production of hydrogen energy, a clean energy source.
[0003] Urea oxidation is a complex six-electron transfer process with relatively slow kinetics, which limits the efficiency and speed of urea oxidation reaction in practical applications. In the urea electro-oxidation reaction, the high initial oxidation potential is a significant problem, which means that a higher voltage is required to start the reaction, increasing energy consumption costs. Therefore, it is of great value to develop and study non-precious metal catalysts with low initial potential, high catalytic efficiency and good stability for use in urea oxidation reaction. Summary of the invention
[0004] The purpose of the embodiment of the present invention is to provide a method for preparing a NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam, aiming to solve the problems raised in the above-mentioned background technology.
[0005] The embodiment of the present invention is implemented as follows: a method for preparing a NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam, comprising the following steps:
[0006] The cut nickel foam is treated with nitric acid, ethanol and deionized water in sequence;
[0007] Na2S2O3 was added to deionized water, and after ultrasonic treatment, it was transferred to a polytetrafluoroethylene liner, and the treated nickel foam was placed in it to carry out the first hydrothermal reaction, and then cooled to room temperature and washed to obtain Ni3S2 / NF;
[0008] Ni(NO3)2·6H2O and Na2MoO4·2H2O were added to deionized water, and after ultrasonic treatment, they were transferred to a polytetrafluoroethylene liner, and Ni3S2 / NF was placed in it for the second hydrothermal reaction. The reaction was then cooled to room temperature, washed, and dried to obtain NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam.
[0009] Preferably, in the step of treating the cut nickel foam with nitric acid, ethanol and deionized water in sequence, the treatment is ultrasonic treatment for 10-15 minutes, and the concentration of the nitric acid is 1-1.2M.
[0010] Preferably, in the step of adding Na2S2O3 into deionized water, Na2S2O3:water (mmol:mL)=2-6:20.
[0011] Preferably, in the step of adding Na2S2O3 into deionized water, Na2S2O3:water (mmol:mL)=4:20.
[0012] Preferably, in the first hydrothermal reaction step, the temperature is 100-150° C. and the time is 6-18 h.
[0013] Preferably, in the first hydrothermal reaction step, the temperature is 120° C. and the time is 12 h.
[0014] Preferably, in the step of adding Ni(NO3)2·6H2O and Na2MoO4·2H2O into deionized water, Ni(NO3)2·6H2O:Na2MoO4·2H2O:water (mmol:mmol:mL)=0.5~1:0.5~1:20.
[0015] Preferably, in the step of adding Ni(NO3)2·6H2O and Na2MoO4·2H2O into deionized water, Ni(NO3)2·6H2O:Na2MoO4·2H2O:water (mmol:mmol:mL)=0.5:1:20.
[0016] Preferably, in the second step of hydrothermal reaction, the temperature is 130-180° C. and the time is 2-8 h.
[0017] Preferably, in the step of performing the second hydrothermal reaction, the temperature is 160° C. and the time is 5 h.
[0018] Another object of an embodiment of the present invention is to provide a NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam, which is prepared by the above-mentioned preparation method.
[0019] Another object of the embodiments of the present invention is to provide an application of NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam in electrocatalytic urea oxidation.
[0020] Preferably, the NiMoO4 / Ni3S2 electrocatalytic material loaded on the nickel foam is placed in an electrochemical reaction cell as a working electrode, the reference electrode is Hg / HgO, the counter electrode is a platinum sheet, and the electrolyte is a mixed solution of KOH solution and urea solution, and the urea oxidation reaction is driven when power is turned on.
[0021] Preferably, the potential applied during the power-on is 1.1-1.6 V compared to the RHE electrode.
[0022] The embodiment of the present invention provides a method for preparing a NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam, wherein NiMoO4 / Ni3S2 / NF (i.e. NiMoO4 / Ni3S2 loaded on nickel foam) is synthesized by a two-step hydrothermal method using simple and readily available raw materials. The preparation method is simple, the required equipment and raw materials are abundant and inexpensive, easy to obtain, easy to repeat, easy to control costs in industrial production, suitable for large-scale production, and stable material quality.
[0023] The prepared nickel foam loaded with NiMoO4 / Ni3S2 electrocatalytic material was used as the working electrode. In 1M KOH and 0.33M urea solution, only 1.338V (relative to the standard hydrogen electrode) was required to obtain 10mA cm -2 The current density is used to drive the UOR, and when it reaches 100 mA cm -2 The current density is only 1.357V (relative to the standard hydrogen electrode). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 An XRD characterization diagram of a NiMoO4 / Ni3S2 electrocatalytic material supported on nickel foam provided in Example 1;
[0025] Figure 2a This is the full XPS spectrum of a NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam provided in Example 1. Figure 2b is the Ni 2p fine spectrum, and Figure 2c is the Mo 3d fine spectrum. Figure 2d is the S2p fine spectrum;
[0026] Figure 3a The cyclic voltammetry curve of the sample prepared in Example 1 in a mixed electrolyte of KOH and urea is shown in FIG. Figure 3b is the double-layer capacitance value of the sample prepared in Example 1 in a mixed electrolyte of KOH and urea, Figure 3c is the cyclic voltammetry curve of Comparative Example 1, Figure 3d is the double-layer capacitance value of comparative example 1, Figure 3e is the cyclic voltammetry curve of Comparative Example 2, Figure 3f is the double-layer capacitance value of Comparative Example 2;
[0027] Figure 4 Comparison of LSV curves of samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 in a mixed electrolyte of KOH and urea. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0029] A NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam, the preparation method of which comprises the following steps:
[0030] S1. Cut the nickel foam NF into a rectangle of 2×3 cm, and ultrasonicate the cut nickel foam NF in 1M HNO3 for 10 min, in ethanol for 10 min, and in deionized water for 10 min.
[0031] S2, dissolve 0.316-0.948g Na2S2O3 in 20mL deionized water, transfer to a polytetrafluoroethylene liner after ultrasonic treatment for 20min, put in the treated nickel foam, react at 100-150℃ for 6-18h, cool to room temperature, wash with deionized water to obtain Ni3S2 / NF;
[0032] S3, 0.145-0.29g Ni(NO3)2·6H2O and 0.12-0.24g Na2MoO4·2H2O were dissolved in 20mL deionized water, and after ultrasonication for 20min, the mixture was transferred to a polytetrafluoroethylene liner, and Ni3S2 / NF was placed in the liner. The reaction was carried out at 130-180℃ for 2-8h, and the mixture was cooled to room temperature, washed with deionized water, and dried in an oven at 80℃ for 1h to obtain NiMoO4 / Ni3S2 / NF.
[0033] The above-mentioned NiMoO4 / Ni3S2 / NF is used as an electrocatalytic material in the electrocatalytic urea oxidation, which specifically includes the following steps: a single electrolytic cell is set as an electrochemical reaction cell, a three-electrode system is adopted, NiMoO4 / Ni3S2 / NF is used as a working electrode, the reference electrode is Hg / HgO, the counter electrode is a platinum sheet, the electrolyte is 1M KOH solution and 0.33M urea solution, and the potential applied when power is turned on is 1.1V-1.6V compared to the RHE electrode.
[0034] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0035] Example 1: A nickel foam loaded NiMoO4 / Ni3S2 electrocatalytic material, the preparation method of which is as follows:
[0036] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene liner after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 12 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene liner, and Ni3S2 / NF was placed in it. The reaction was carried out at 160°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4 / Ni3S2 / NF.
[0037] Example 2: A nickel foam loaded NiMoO4 / Ni3S2-2mmol electrocatalytic material, the preparation method of which is as follows:
[0038] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 2 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene bushing after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 12 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene bushing, and Ni3S2-2mmol / NF was placed in it. The reaction was carried out at 160°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4 / Ni3S2-2mmol / NF.
[0039] Example 3: A nickel foam loaded NiMoO4 / Ni3S2-6mmol electrocatalytic material, the preparation method of which is as follows:
[0040] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 6 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene bushing after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 12 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene bushing, and Ni3S2-6mmol / NF was placed in it. The reaction was carried out at 160°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4 / Ni3S2-6mmol / NF.
[0041] Example 4: A NiMoO4 / Ni3S2-6h electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0042] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene liner after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 6 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene liner, and Ni3S2-6h / NF was placed in it. The reaction was carried out at 160°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4 / Ni3S2-6h / NF.
[0043] Example 5: A NiMoO4 / Ni3S2-18h electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0044] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene liner after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 18 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene liner, and Ni3S2-18h / NF was placed in it. The reaction was carried out at 160°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4 / Ni3S2-18h / NF.
[0045] Example 6: A NiMoO4 / Ni3S2-100°C electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0046] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene bushing after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 100°C for 12 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene bushing, and placed in Ni3S2-100°C / NF. The reaction was carried out at 160°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4 / Ni3S2-100°C / NF.
[0047] Example 7: A NiMoO4 / Ni3S2-150°C electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0048] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene bushing after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 150°C for 12 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene bushing, and Ni3S2-150°C / NF was placed in it. The reaction was carried out at 160°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4 / Ni3S2-150°C.
[0049] Example 8: A nickel foam loaded Ni1Mo1O4 / Ni3S2 electrocatalytic material, the preparation method of which is as follows:
[0050] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene bushing after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 12 hours, cooled to room temperature, and washed with deionized water; 1 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene bushing, and Ni3S2 / NF was placed in it. The reaction was carried out at 160°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain Ni1Mo1O4 / Ni3S2 / NF.
[0051] Example 9: A Ni2Mo1O4 / Ni3S2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0052] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene bushing after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 12 hours, cooled to room temperature, and washed with deionized water; 1 mmol of nickel nitrate hexahydrate and 0.5 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene bushing, and Ni3S2 / NF was placed in it. The reaction was carried out at 160°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain Ni2Mo1O4 / Ni3S2 / NF.
[0053] Example 10: A NiMoO4-8h / Ni3S2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0054] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene bushing after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 12 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene bushing, and Ni3S2 / NF was placed in it. The reaction was carried out at 160°C for 8 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4-8h / Ni3S2 / NF.
[0055] Example 11: A NiMoO4-2h / Ni3S2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0056] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene bushing after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 12 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene bushing, and Ni3S2 / NF was placed in it. The reaction was carried out at 160°C for 2 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4-2h / Ni3S2 / NF.
[0057] Example 12: A nickel foam loaded NiMoO4-180°C / Ni3S2 electrocatalytic material, the preparation method of which is as follows:
[0058] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene bushing after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 12 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene bushing, and Ni3S2 / NF was placed in it. The reaction was carried out at 180°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4-180°C / Ni3S2 / NF.
[0059] Example 13: A NiMoO4-130°C / Ni3S2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0060] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material, dissolved in 20 mL of deionized water, and transferred to a polytetrafluoroethylene liner after ultrasonic treatment for 20 minutes, and the treated nickel foam was placed in it. The reaction was carried out at 120°C for 12 hours, cooled to room temperature, and washed with deionized water; 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, ultrasonicated for 20 minutes, transferred to a polytetrafluoroethylene liner, and Ni3S2 / NF was placed in it. The reaction was carried out at 130°C for 5 hours, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 hour to obtain NiMoO4-130°C / Ni3S2 / NF.
[0061] Comparative Example 1: A Ni3S2 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0062] The cut nickel foam was treated with nitric acid, ethanol and deionized water in turn. 4 mmol of analytical grade sodium thiosulfate was selected as the raw material and dissolved in 20 mL of deionized water. After ultrasonic treatment for 20 min, it was transferred to a polytetrafluoroethylene liner and the treated nickel foam was placed in it. The reaction was carried out at 120 °C for 12 h, cooled to room temperature, washed with deionized water, and dried in an oven at 80 °C for 1 h to obtain Ni3S2 / NF.
[0063] Comparative Example 2: A NiMoO4 electrocatalytic material loaded on nickel foam, the preparation method of which is as follows:
[0064] 0.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 20 mL of deionized water, and after ultrasonic treatment for 20 min, they were transferred to a polytetrafluoroethylene liner and placed in Ni3S2 / NF. The mixture was reacted at 160°C for 8 h, cooled to room temperature, washed with deionized water, and dried in an oven at 80°C for 1 h to obtain NiMoO4 / NF.
[0065] Performance Test:
[0066] The NiMoO4 / Ni3S2 / NF sample prepared in Example 1 was analyzed to obtain the XRD spectrum as shown in Figure 1 The full XPS spectrum is shown in Figure 2a As shown in the figure, the Ni 2p fine spectrum is as follows Figure 2b As shown, the Mo 3d fine spectrum is as follows Figure 2b As shown, the S2p fine spectrum is as follows Figure 2d As shown;
[0067] The samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to cyclic voltammetry test, and the double-layer capacitance value was calculated. The cyclic voltammetry curve of the sample prepared in Example 1 in a mixed electrolyte of KOH and urea is shown in FIG. Figure 3a As shown, the double layer capacitance value results are as follows Figure 3b As shown, the cyclic voltammetry curve of Comparative Example 1 is as follows Figure 3c As shown, the double layer capacitance value results are as follows Figure 3d As shown, the cyclic voltammetry curve of Comparative Example 2 is as follows Figure 3e As shown, the double layer capacitance value results are as follows Figure 3f As shown;
[0068] The samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 were used as electrocatalytic materials to test their effects in electrocatalytic urea oxidation-assisted overall water decomposition. The specific operation was as follows:
[0069] A mixed solution of 1M potassium hydroxide and 0.33M urea was used as the electrolyte, three samples were used as working electrodes, platinum sheets were used as counter electrodes, and mercury / mercury oxide electrodes were used as reference electrodes. The potential was controlled at 0.2V-0.8V relative to the mercury / mercury oxide electrodes. The electrochemical workstation was used to test and the results were obtained. Figure 4 The LSV curve shown in Figure 4 It can be seen that the material prepared in the embodiment of the present invention only needs 1.338V (relative to the standard hydrogen electrode) to obtain 10mA cm -2 The current density is used to drive the UOR, and when it reaches 100 mA cm -2 The current density is only 1.357V (relative to the standard hydrogen electrode).
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam, characterized in that: The following steps are involved: The cut nickel foam is treated with nitric acid, ethanol and deionized water in sequence; Na2S2O3 was added to deionized water, and after ultrasonic treatment, it was transferred to a polytetrafluoroethylene liner, and the treated nickel foam was placed in it to carry out the first hydrothermal reaction, and then cooled to room temperature and washed to obtain Ni3S2 / NF; Ni(NO3)2·6H2O and Na2MoO4·2H2O were added to deionized water, and after ultrasonic treatment, they were transferred to a polytetrafluoroethylene liner, and Ni3S2 / NF was placed in it for the second hydrothermal reaction. The reaction was then cooled to room temperature, washed, and dried to obtain NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam.
2. The method for preparing the NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam according to claim 1, characterized in that: In the step of treating the cut nickel foam with nitric acid, ethanol and deionized water in sequence, the treatment is ultrasonic treatment for 10-15 minutes, and the concentration of the nitric acid is 1-1.2M.
3. The method for preparing the NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam according to claim 1, characterized in that: In the step of adding Na2S2O3 into deionized water, Na2S2O3:water (mmol:mL)=2-6:
20.
4. The method for preparing the NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam according to claim 1, characterized in that: In the first step of the hydrothermal reaction, the temperature is 100-150°C and the time is 6-18h.
5. The method for preparing the NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam according to claim 1, characterized in that: In the step of adding Ni(NO3)2·6H2O and Na2MoO4·2H2O into deionized water, Ni(NO3)2·6H2O:Na2MoO4·2H2O:water (mmol:mmol:mL)=0.5~1:0.5~1:
20.
6. The method for preparing the NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam according to claim 1, characterized in that: In the second step of hydrothermal reaction, the temperature is 130-180°C and the time is 2-8h.
7. A NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the NiMoO4 / Ni3S2 electrocatalytic material loaded on nickel foam as claimed in claim 7 in electrocatalytic urea oxidation.
9. The use according to claim 8, characterized in that: The NiMoO4 / Ni3S2 electrocatalytic material loaded on the nickel foam is placed in an electrochemical reaction cell as a working electrode, the reference electrode is Hg / HgO, the counter electrode is a platinum sheet, and the electrolyte is a mixed solution of KOH solution and urea solution. The urea oxidation reaction is driven when power is turned on.
10. The use according to claim 9, characterized in that: The potential applied during the power-on is 1.1-1.6 V compared to the RHE electrode.
